A Cervical Spine Gunshot Injury without Bone or Neurological Deficits - Amer, Majed A. (University of Science and Technology, Sana'a, 2015)
INTRODUCTION: Missile injuries of the spine has been reported literatures, The neurosurgical concern in such injuries is the degree of damage sustained during the bullet traversing the bony and neural tissue and their effect on long term follow up. PRESENTATIION: This report describes an interesting case of gunshot traversing the cervical vertebral body, the spinal cord and the posterior element without appearance of any bony destruction or neurological deficit. DISCUSSION: The patient was managed conservatively with long term follow up clinically and radiological with excellent recovery. CONCLUSION: Surgery should be served for specific cases according to the severity of the trauma and its effect.